Arsenic in the Iberoamerican Region: The Iberoarsen Network and a possible economic solution for arsenic removal in isolated rural zones - Morgada, Maria Eugenia (2008)
In this work, a short description of the problematic of arsenic in Iberoamerica will be given, indicating the affected geographical regions and their incidence on the quality of life of the populations. In Argentina, Chile, Bolivia, Peru, Ecuador and Mexico, at least 4 million people depend on water sources with toxic concentrations of arsenic. While in these countries the problem is known since decades, in Uruguay, Brazil, Nicaragua, Honduras and El Salvador, the problem has been detected or investigated only in last years, and, in other Latinamerican countries, the studies began only recently. In Spain and Portugal the problem of As is becoming increasingly important. The presence of As in drinking waters, together with poverty and malnutrition, causes the incidence of CERHA (chronic endemic regional hydroarsenicism, HACRE in Spanish), an illness that provokes serious problems like skin lesions and even cancer. The activities of the IBEROARSEN Network of the CYTED Program, an Iberoamerican project that aims at the interconnection of groups devoted to arsenic R&D, trying to find solutions to this problem in the region, will be described. In addition, results of evaluation of the efficiency of two very simple low-cost methods for As removal in plastic bottles using solar light, one of them using heterogeneous photocatalysis with TiO2 immobilized on the walls followed by iron addition, and another one based on the use of zerovalent iron, which employs very cheap materials, are presented. The study was performed with synthetic and natural waters of rural, isolated, poor populations, not connected to the drinking water network of the provinces of Tucumán and Santiago del Estero, Argentina. For HP tests, synthetic as well as natural samples containing arsenic placed in bottles internally covered by a TiO2 layer and exposed to solar or artificial UV light followed by an addition of an iron source resulted in As concentration well below the national standards. For ZVI tests, iron wool demonstrated to be a better iron source than packing wire for As removal. Solar irradiation, in synthetic as well as in natural samples, seems to definitively improve As removal, avoiding the use of high amounts of iron. Although both HP and ZVI gave similar results, the use of the first one could be superior due to the ability of removing simultaneously As, organic matter, toxic metals and microbiological contamination.